2023
DOI: 10.1111/joms.12913
|View full text |Cite
|
Sign up to set email alerts
|

How Does CEO Decision Style Influence Firm Performance? The Mediating Role of Speed and Innovativeness in New Product Development

Abstract: Although chief executive officers (CEOs) are the primary decision‐makers in their firms, there has been little research on how CEOs' decision styles affect firm performance. This study explores the relationships between firm performance and two key dimensions of CEO decision style, namely the use of heuristics and decision standards. We conceptualize the speed and innovativeness of new product development (NPD) as mediators in these relationships. An empirical analysis of 1046 German firms indicates that CEOs'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 192 publications
1
6
0
Order By: Relevance
“…This research is in line with studies that have introduced the creation of participation as one of the successful approaches to increasing productivity (Dionne et al, 2019; Hertz et al, 2016; Kruse et al, 2023; Vink et al, 2006). However, the gap that exists in the previous research is that they did not clarify the process of constructing participation and how to create participation.…”
Section: Introductionsupporting
confidence: 85%
See 2 more Smart Citations
“…This research is in line with studies that have introduced the creation of participation as one of the successful approaches to increasing productivity (Dionne et al, 2019; Hertz et al, 2016; Kruse et al, 2023; Vink et al, 2006). However, the gap that exists in the previous research is that they did not clarify the process of constructing participation and how to create participation.…”
Section: Introductionsupporting
confidence: 85%
“…One of the factors affecting productivity is the way managers make decisions, which may be individually or with the participation of employees (collectively) (Low & Mohr, 2001; Sinnaiah et al, 2023). If managers’ decisions are collective, productivity indicators will improve (Dionne et al, 2019; Hertz et al, 2016; Kruse et al, 2023).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Resick et al's (2023) study, reported in this special issue, contributes significantly to this research stream by showing that CEOs’ core self‐evaluations can lead to adaptive, as opposed to maladaptive, strategic behaviour, as a function of several contingent features of the competitive environment in which their firms are embedded. Similarly, the study by Kruse et al (2023) makes a significant contribution to this line of inquiry by demonstrating that in the domain of NPD, top managers’ heuristics can be an effective decision aid, helping to create value for firms by accelerating the development of new products.…”
Section: Future Research Directionsmentioning
confidence: 99%
“…In the second of these pieces, Kruse et al (2023) explicitly position their study of new product development (NPD) decisions on the part of the CEOs of 1046 German firms as a response to calls for additional generalizable evidence pertaining to the ecological rationality of heuristics in managerial contexts. The authors develop and test the theoretical claim that the speed and innovativeness of NPD mediates the impact of CEOs' decision styles on the performance of their firms.…”
Section: Alternative Conceptions Of Bounded Rationality and Heuristicsmentioning
confidence: 99%